2017
DOI: 10.1021/acs.jmedchem.7b00527
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer Functionalization of Nanosystems for Glioblastoma Targeting through the Blood–Brain Barrier

Abstract: Polymeric nanoparticles (PNPs) may efficiently deliver in vivo therapeutics to tumors when conjugated to specific targeting agents. Gint4.T aptamer specifically recognizes platelet-derived growth factor receptor β and can cross the blood-brain barrier (BBB). We synthesized Gint4.T-conjugated PNPs able of high uptake into U87MG glioblastoma (GBM) cells and with astonishing EC value (38 pM) when loaded with a PI3K-mTOR inhibitor. We also demonstrated in vivo BBB passage and tumor accumulation in a GBM orthotopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
98
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(102 citation statements)
references
References 28 publications
4
98
0
Order By: Relevance
“…Highly specific tools, such as aptamers, may represent molecular probes for labeling the targets on tumor samples and thus helping to patient stratification. In addition, accessibility of cell surface receptors for targeting with aptamers will allow not only molecular imaging but also the direct delivery of drugs to relevant cancer cells [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Highly specific tools, such as aptamers, may represent molecular probes for labeling the targets on tumor samples and thus helping to patient stratification. In addition, accessibility of cell surface receptors for targeting with aptamers will allow not only molecular imaging but also the direct delivery of drugs to relevant cancer cells [14]. …”
Section: Introductionmentioning
confidence: 99%
“…In this study, we developed multi‐walled carbon nanotubes (MWCNTs) modified with mannose (Man‐MWCNTs) as a specific target delivery system to DCs. Compared with passive target delivery, decorating with targeting ligands which can actively recognize specific receptors on the target cell is much more efficient . Chicken egg ovalbumin (OVA), a standard antigenic protein, was chosen and loaded onto Man‐MWCNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with passive target delivery, decorating with targeting ligands which can actively recognize specific receptors on the target cell is much more efficient. [28] Chicken egg ovalbumin (OVA), a standard antigenic protein, [29] was chosen and loaded onto Man-MWCNTs. (Scheme 1) It was found that this system could be highly engulfed by DCs and efficiently induce DCs maturation in vitro, demonstrating its potential as an antigen-adjuvant nanovector for further application in vaccine development.…”
Section: Introductionmentioning
confidence: 99%
“…Upon treatment with 15 a and 15 b,w ee valuated the phosphorylation of 4EBP1, aw ell-established substrate of mTOR [27] and of p70 S6 kinase, which acts predominantly downstream of PI3K, [28] in our GBM cell line panel.I nterestingly, 15 b was the most effective compound at inhibiting PI3K/mTOR biochemicala ctivities in both U251 and DBTRG cells (Figure 4a nd FiguresS2A and S2B, Supporting Information), confirming the consistently higher efficiency of this compound in cytotoxicity studies (see above). Upon treatment with 15 a and 15 b,w ee valuated the phosphorylation of 4EBP1, aw ell-established substrate of mTOR [27] and of p70 S6 kinase, which acts predominantly downstream of PI3K, [28] in our GBM cell line panel.I nterestingly, 15 b was the most effective compound at inhibiting PI3K/mTOR biochemicala ctivities in both U251 and DBTRG cells (Figure 4a nd FiguresS2A and S2B, Supporting Information), confirming the consistently higher efficiency of this compound in cytotoxicity studies (see above).…”
mentioning
confidence: 99%
“…Therefore, we next sought to investigate whether the cytotoxic activity of these compounds toward GBM cells is indeed correlated with their ability to inhibit PI3K and mTOR kinases. Upon treatment with 15 a and 15 b,w ee valuated the phosphorylation of 4EBP1, aw ell-established substrate of mTOR [27] and of p70 S6 kinase, which acts predominantly downstream of PI3K, [28] in our GBM cell line panel.I nterestingly, 15 b was the most effective compound at inhibiting PI3K/mTOR biochemicala ctivities in both U251 and DBTRG cells (Figure 4a nd FiguresS2A and S2B, Supporting Information), confirming the consistently higher efficiency of this compound in cytotoxicity studies (see above). Ultimately,t he two compounds showed In conclusion, products characterizedb yh igh molecular complexity and great functional group diversity were easily obtained.…”
mentioning
confidence: 99%